Examining the Impact of Problem-Based Learning on Critical Thinking Among Junior High School Students - Nur Amanda; Wahyuningsih (Trigin Institute, 2024)
Problem-based learning (PBL) has gained traction as a pedagogical approach aimed at fostering critical thinking skills among students. This research explores the influence of PBL on the critical thinking ability of junior high school students. Employing a quasi-experimental design, our study compares the critical thinking performance of students engaged in PBL with those receiving traditional instruction. Quantitative analysis reveals significant differences in post-test scores, with students in the PBL group demonstrating higher levels of critical thinking ability. Qualitative insights further illuminate the transformative impact of PBL on student engagement, collaboration, and enjoyment of learning. The findings underscore the efficacy of PBL in promoting critical thinking skills and have practical implications for educators seeking to enhance student learning outcomes. By integrating problem-based learning into the curriculum and providing support and scaffolding to students, educators can create learning environments that empower students to become critical thinkers and lifelong learners capable of navigating the complexities of the modern world.